Feminist Study of Sabiya Novel: Implications for Vocational School: Kemandirian Tokoh Utama Perempuan dalam Novel Sabiya Karya Mellyana Dhian sebagai Bentuk Ekspresi Feminis Serta Rekomendasinya Sebagai Bahan Ajar Teks Novel di SMK - Suciyanti; Muhtarom, Imam; Sugiarti, Dewi Herlina (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
Independence is important for every individual, especially women, to express themselves freely and do whatever they want without depending on others. Independence does not only occur due to the influence of others, but can occur as a result of encouragement from oneself who is already aware of one's identity. This research aims to describe the value of independence contained in the novel Sabiya by Mellyana Dhian. This study uses qualitative research with a descriptive analysis method. The subject of the study uses the novel Sabiya by Mellayana Dhian and the object of the research is the value of independence. The data collection technique used in this study uses the technique of reading, recording and summarizing. The results of the study showed data the value of independence contained in the novel Sabiya by Mellyana Dhian including behavioral autonomy and emotional autonomy. The results of the analysis are then used as recommendations for teaching materials for novel texts in SMK.